Perbedaan Pengaruh Metode Simulation Game (SIG) dengan Audio Visual terhadap Peningkatan Pengetahuan Kesehatan Reproduksi Remaja Putri di SMK Negeri 1 Pujon - Nur Azizah, Hanifah Asgi; Amelia, Coryna Rizky; Dewi, Mustika (Journal of Issues in Midwifery, 2018)
Reproductive health problems in adolescents occurs because teenagers lack knowledge of reproductive health. The results of preliminary study on class X of 10 students by giving a short question through interviews showed that 7 students (70%) of them have less knowledge level about reproductive health especially about young age marriage and HIV. Therefore it is takes socialization efforts with simulation game and audio visual method as an effort to improve students' knowledge about young marriage and HIV / AIDS. This study aims to analyze difference in the influence of counseling method of simulation game with audio visual to increase knowledge of reproductive health of young women in SMK Negeri 1 Pujon. The study design was true-experimental, pre-test design study post-test contrrol group design. Popluasi in this stidy were all students of class X SMK Negeri 1 Pujon amounted to 89 students, the sample used 50 students by using simple random sampling technique. The independent variable were extension method with simulation game and audio visual. The dependent variable is the level of knowledge of young women about reproductive health. The results showed that there were differences between the simulation game method and audio visual to increase the knowledge of X-class girls about reproductive health (p = 0,041). The simulation game method has more effective to increase the knowledge of the girls than the audio visual, because the average score of game simulation knowledge is higher than the average score audio visual (4.80> 3.16). Based on the results of the research, the suggestion for the school that researchers expect special programs as a preventative measure of young marriage and HIV / AIDS in the form of health education where simulation games and audio visual methods can be used as an alternative choice of methods in the implementation of the program.Key words: audio visual, HIV/AIDS, knowledge inprovement, simulation game, young marriage.